Electro-optical characteristics of 808 nm ridge-waveguide lasers operated with high-current nanosecond pulses. (24th March 2017) - Klehr, A; Wünsche, H J; Liero, A; Prziwarka, T; Erbert, G; Wenzel, H; Knigge, A
Abstract: The aim of this paper is to present detailed experimental and theoretical investigations of the behavior of ridge-waveguide (RW) lasers emitting at 808 nm under injection of 3 ns long current pulses with amplitudes higher than 10 A. The RW lasers are based on tensile-strained GaAsP quantum wells embedded in asymmetric and extremely asymmetric AlGaAs based waveguide structures, which differ mainly in the ratio between the thicknesses of the p- and n-type confinement layers. The width of the ridges is 4.4 μ m and the length of the cavities is 3.9 mm. The laser diodes are mounted on an in-house developed high-frequency unit electrically driven by nearly rectangular shaped current pulses with a length of 3 ns and a repetition frequency of 1 MHz. At a pulse current of 15 A maximum pulse powers of 4.0 and 5.4 W are reached for the asymmetric and extremely asymmetric structures, respectively. After turning off the bias a pronounced negative current superimposed by current oscillations caused by the external circuitry appears. Two-dimensional simulations based on a solution of the time-dependent drift-diffusion, waveguide and power-balance equations reveal that a part of the carriers injected into the laser diode does not recombine in the active region and accumulates under the ridge in the bulk layers and beyond the ridge in the active layer. At the end of the electrical pulse the electrons flow back and generate a reverse (negative) current. The simulation exaggerates the achievable output power, in particular for the extremely asymmetric structure. Further theoretical studies are needed to resolve this discrepancy.